Influence Audit Evidence And Materiality Against Lack Detection (Survey At Public Accounting Firms Throughout Dki Jakarta) - Ersyafitri Ersyafitri; Ratna Mappanyuki (Eduvest - Journal of Universal Studies, 2025)
Research purposes This study aims to determine the effect of audit evidence and materiality on fraud detection (survey at public accounting firms in DKI Jakarta). as Respodent. SPSS 25 is used as a tool used to analyze data. The research data used comes from a questionnaire collected using the survey method. The survey was conducted for one month from September 2, 2019 to September 30, 2019. The survey was carried out in the DKI area. The results of the study and data analysis used simple linear regression. Research result Based on the analytical results, it can be seen that the audit evidence and materiality variables have no effect on fraud detection. Research limitations / limitations The studies in this study have not been able to answer all the causal phenomena of fraud detection. The data used is still small, as many as 176 auditors and the object used as the unit of analysis is only one type of auditor who works in a public accounting firm. PractitionersThis study encourages all auditors, especially those who work in public accounting firms, to have a professional suspicion in performing their duties in order to be able to detect fraud in the company. Originality / value: In this study the focus is on proving whether audit evidence and materiality will give an Auditor the ability to detect fraud.